This preview shows page 1. Sign up to view the full content.
Unformatted text preview: , g ( n + 2) = 2 g ( n + 1) + 6 g ( n ) , n . 5. Find an explicit solution for the recurrence { h ( n ) } n satisfying h (0) = 1 , h (1) = 4 , h ( n + 2) = 4 h ( n + 1)4 h ( n ) , n . * ( extra credit ) F n , n , are the Fibonacci numbers: F = 0 , F 1 = 1 , F n +2 = F n +1 + F n , n . Prove that n X k =0 n + k 2 k = F 2 n +1 , n . 1...
View
Full
Document
This note was uploaded on 04/23/2008 for the course CSE 21 taught by Professor Graham during the Spring '07 term at UCSD.
 Spring '07
 Graham

Click to edit the document details